Improving Islamic Religious Education Learning Achievement Through Demonstration Methods for Elementary School Students 091590 Serbelawan - Manurung, Eliana Saprida; Suyanti; Nurhayati, Siti; Ramadhani, Rivo; Iziati (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2024)
This study aims to improve the learning achievement of Islamic Religious Education through the demonstration method in grade IV students of SD Negeri 091590 Serbelawan. The background of this study is based on the low learning outcomes of students due to the use of conventional learning methods that do not actively involve students. The demonstration method was chosen as a solution to help students understand practical worship material through direct practice. This study uses the Classroom Action Research method consisting of two cycles, where each cycle includes the planning, implementation, observation, and reflection stages. The results of the study showed that the demonstration method was able to improve students' understanding, both from cognitive, affective, and psychomotor aspects. The percentage of student learning completion increased from 60% in cycle I to 85% in cycle II. In addition, the demonstration method also made students more active and enthusiastic in participating in learning. The conclusion of this study is that the demonstration method is effective in improving Islamic Religious Education learning achievement, and is able to encourage active student participation in learning. Therefore, this method is recommended as an alternative learning method in improving the quality of Islamic Religious Education learning